INFLUENCE OF SELECTED PINION CUTTING TECHNOLOGICAL PARAMETERS ON KINEMATIC QUALITY OF SPIRAL BEVEL GEARS - Jadwiga PISULA; Mieczysław PŁOCICA (Scientific Journal of Silesian University of Technology. Series Transport, 2014)
The article evaluated the effect of selected process parameters on the accuracy of kinematic spiral bevel gear pair. The changes of technological parameters were analyzed using a proprietary, non-commercial support system for design bevel gears. The effect of the parameter changes were observed in the motion graph of the gear and pinion mesh with ratio 4:99. It has been shown that the modifications of technological parameters can produce a small positive effect on fluency of motion, but predominantly have a negative impact on the accuracy of kinematic.